CYTOTOXICITY, ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF THE LEAVES AND STEM BARK EXTRACTS OF VITELLARIA PARADOXA (FUDMA JOURNAL OF SCIENCES, 2023)
The effective use of Vitellariaparadoxa in traditional medicine for treatment of various ailments including inflammation, fever, skin irritation, dermatitis, sunburn, rheumatism, diarrhea, stomach ache and ulcers are well established. This study focused on the cytotoxicity of the plant parts using Brine Shrimp Lethality Assay (BSLA), antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and antimicrobial activity against Bacillus cereus, Staphylococcus aureus, Kleibsiella pneumonia and Escherichia coli using disc diffusion and minimum inhibitory concentration methods. Result of cytotoxicity showed that the leaves crude extract (VPL 01) is more cytotoxic with LC50 15.17µg/mL followed by the methanol fraction of both the leaves (VPL 04) and the stem bark (VPS 04) with LC50 values 23.21 and 19.35µg/mL respectively. The result of the antioxidant assay obeys the Beer-Lambert law over the useful range with both the leaves and stem back of Vitellariaparadoxa showing great antioxidant potency in all fractions tested. Themethanolic fraction standout above other factions with IC50 of 9.64µg/mL and 6.50µg/mL for the leaves and stem bark fractions respectively followed by the moderately polar ethyl acetate fraction which recorded IC5016.96µg/mLand16.38µg/mL for leaves and stem back in comparison with standard ascorbic acid and BHT which recorded 4.77µg/mL and 9.18µg/mL respectively. The antimicrobial activity showed that the ethanol leaves extract had the maximum zone of inhibition against the entire test organisms, while the methanol fraction showed maximum inhibition against B. cereus (18±0.73 mm), S. aureus (19±1.41 mm) and K. pneumonia (19±0.03 mm) with MIC values of 62.5µg/mL for all the organisms respectively. These studies indicated
Keywords: Vitellariaparadoxa, cytotoxicity, antioxidant, antimicrobial